2021
DOI: 10.1038/s41598-021-83414-7
|View full text |Cite
|
Sign up to set email alerts
|

A proof-of-concept study of the in-vivo validation of a computational fluid dynamics model of personalized radioembolization

Abstract: Radioembolization (RE) with yttrium-90 (90Y) microspheres, a transcatheter intraarterial therapy for patients with liver cancer, can be modeled computationally. The purpose of this work was to correlate the results obtained with this methodology using in vivo data, so that this computational tool could be used for the optimization of the RE procedure. The hepatic artery three-dimensional (3D) hemodynamics and microsphere distribution during RE were modeled for six 90Y-loaded microsphere infusions in three pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…The first observation is that the imposed blood flow split differs from the predicted or calculated microsphere distribution (see Figures 5,7,9 and 11). This finding is not novel, it is indeed observed in previous studies that used a microcatheter to inject the microspheres [8] or the studies that used the particle release maps [7,9,26] as a research tool-particle release maps correlate each point in the injection cross-sectional plane with the computational domain outlet from which microspheres would exit. Even if a blood flow split-matching microsphere distribution can be achieved [5], this cannot be assumed as a general rule.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The first observation is that the imposed blood flow split differs from the predicted or calculated microsphere distribution (see Figures 5,7,9 and 11). This finding is not novel, it is indeed observed in previous studies that used a microcatheter to inject the microspheres [8] or the studies that used the particle release maps [7,9,26] as a research tool-particle release maps correlate each point in the injection cross-sectional plane with the computational domain outlet from which microspheres would exit. Even if a blood flow split-matching microsphere distribution can be achieved [5], this cannot be assumed as a general rule.…”
Section: Discussionsupporting
confidence: 60%
“…The CFD model (type of geometry plus governing equations plus type of boundary conditions) and the simulation strategy (simulation of one cardiac cycle where micro-spheres are injected plus sufficient additional cardiac cycles to ensure that most of the injected microspheres exit the computational domain) used in this study have been recently validated in vivo in a proof-of-concept study, where the CFD model was defined using pre-RE imaging techniques and the simulated segment-to-segment microsphere distribution was compared with the measured segment-to-segment activity distribution taken from post-RE imaging techniques [26].…”
Section: Solver Settingsmentioning
confidence: 99%
“…Investigations of the microscopic depositions of microspheres can be investigated in vivo by imaging (SPECT, PET and MRI) or simulated in vitro by computational or artificial models of the hepatic arterial system. An excellent agreement was recently demonstrated between the microscopic deposition of microspheres simulated with a computational model and the real distribution observed in patients with 90 Y PET/CT [ 37 ], especially with time- of-flight (TOF)-PET systems [ 38 , 39 ].…”
Section: Impact At a Microscopic Level-microdosimetrymentioning
confidence: 80%
“…These and other developments could be explored using computational techniques, i.e., using computer simulations. For example, a recent study has confirmed that computer simulations of hepatic artery hemodynamics and radioactive microsphere transport can predict the segment-to-segment microsphere distribution [ 10 ].…”
Section: Introductionmentioning
confidence: 99%